EFFECTIVE METHODS AND TOOLS FOR TEACHING ENGLISH REMOTELY (International journal of artificial intelligence, 2026)
The article Effective Methods and Tools for Teaching English Remotely examines contemporary strategies and digital technologies used to deliver high-quality English language instruction in online learning environments. The study highlights the importance of adapting traditional teaching methods to virtual platforms in order to maintain student engagement, interaction, and consistent language practice. Particular attention is given to communicative teaching approaches, task-based learning, and blended instructional models that promote active participation and real-life language use.The article analyzes a variety of digital tools, including video conferencing platforms, learning management systems, interactive applications, and online assessment tools. These technologies are evaluated in terms of accessibility, usability, and effectiveness in developing speaking, listening, reading, and writing skills. The study also emphasizes the role of multimedia resources, such as videos, podcasts, and online games, in supporting diverse learning styles and sustaining motivation.